An intelligent light-driven thermoelectric conversion system through the thermosensitive phase transition of vanadium dioxide. Issue 14 (21st March 2019) - Zhang, Yuang; Umair, Malik Muhammad; Jin, Xin; Lu, Rongwen; Zhang, Shufen; Tang, Bingtao
Abstract : A new intelligent light-driven thermoelectric conversion system was designed, which contained PS/Fe2 O3 -GNS, VO2 film and a thermoelectric module. This system can realize light-thermal-electric conversion and obtain a stable current under sunlight. Abstract : Solar thermoelectric generation (STEG) is an environmentally-friendly, safe, and economical technique that can be used for sustainable solar energy utilization. Efficient and stable STEG depends on strong light absorption and stable temperature difference. Herein, we constructed a new intelligent light-driven thermoelectric conversion system with VO2, polystyrene/Fe2 O3 -graphene nanosheets (PS/Fe2 O3 -GNS), and a thermoelectric module. The system can realize light-thermal-electric conversion and obtain a stable current owing to the infrared light transmittance switch of the VO2 film, high visible-light absorbing ability of PS/Fe2 O3 -GNS, and thermoelectric effect of the thermoelectric module. Furthermore, the new system can operate normally under sunlight, indicating the prospect of practical application.